2016
DOI: 10.1016/j.ijms.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Multistage mass spectrometry of phospholipids using collision-induced dissociation (CID) and metastable atom-activated dissociation (MAD)

Abstract: We herein demonstrate an approach to gas phase ion manipulation that provides MS3-level CID spectra of phospholipid radical cations that are almost independent of the original charging adduct ions. In the MS2 He-MAD spectra of the protonated, sodiated and potassiated adducts of POPC, the different adducts induce different primary fragmentation pathways and provide significantly different spectra, as is commonly observed by other activation methods. In separate experiments, the even-electron adduct ions ([M+H]+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 47 publications
(52 reference statements)
0
38
0
Order By: Relevance
“…3133 Yang et al employed a strategy in which the variation in abundances of neutral loss products were monitored as a function of double bond position to identify both the double bond position and quantify relative amounts of fatty acid isomers. 34 Additional methods have focused on novel ion activation techniques including radical-directed dissociation (RDD) via 266 nm photodissociation followed by CID 3537 , ozone induced dissociation (OzID) 3840 , electronic impact excitation of ions from organics (EIEIO) 41 , metastable atom-activated dissociation (MAD) 42,43 and electron transfer dissociation (ETD) 44 . In parallel studies Pham et al explored non-covalent complexation of 4-iodobenzoic acid, 4-iodoaniline or 4-iodobenzoyl 18-crown-6 to glycerophospholipids and reactions of 4-iodobenzyl alcohol with fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…3133 Yang et al employed a strategy in which the variation in abundances of neutral loss products were monitored as a function of double bond position to identify both the double bond position and quantify relative amounts of fatty acid isomers. 34 Additional methods have focused on novel ion activation techniques including radical-directed dissociation (RDD) via 266 nm photodissociation followed by CID 3537 , ozone induced dissociation (OzID) 3840 , electronic impact excitation of ions from organics (EIEIO) 41 , metastable atom-activated dissociation (MAD) 42,43 and electron transfer dissociation (ETD) 44 . In parallel studies Pham et al explored non-covalent complexation of 4-iodobenzoic acid, 4-iodoaniline or 4-iodobenzoyl 18-crown-6 to glycerophospholipids and reactions of 4-iodobenzyl alcohol with fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Radical ions have been observed to react with residual oxygen during their confinement in electrodynamic ion traps, which was also noted for the ETD-generated z • ions [28,29] and MAD-generated [POPC] +• radical ions [30].…”
Section: Resultsmentioning
confidence: 67%
“…One of the more abundant background ions has a massto-charge ratio of 184 (see Supplementary Figure S2, for example), does not fragment using CID, and reacts with residual oxygen to form adducts at M + 16 (m/z 200) and M + 32 (m/z 216). CID of the M + 16 and M + 32 adducts re-forms the original reagent anion at m/z 184, indicating that the reagent is probably polycyclic/aromatic and almost certainly a radical (vide infra) [28][29][30]. Figure 1c shows that these reagent anions are reasonably effective at forming c and z ions from the 3+ precursor of substance P. Fortunately, this charge reduction mechanism can be minimized by raising the LMCO during CTD activation to prevent the co-accumulation of reagent anions, with the caveat that increasing the LMCO also limits the observable range of product ions for CTD.…”
Section: Resultsmentioning
confidence: 99%
“…It has reported that when the radical species are stored in the electrodynamic ion trap at room temperature, they often react with residual oxygen. The addition of O or O 2 to distonic radical cations has been observed in ETD [41], fs-LID [42], He-MAD [43], and He-CTD [37]. However, oxygen-attachment was not observed for either [Chain A] 2+ or [Chain B] 3+ , indicating that the two types of individual chain adduct ions are more likely to be even-electron species, or that the radical resides on the sulfur atoms and does not undergo the typical oxygen addition.…”
Section: Resultsmentioning
confidence: 99%